Identifying individuals for primary cardiovascular disease prevention in UK general practice: priorities and resource implications. - Holt, T; Thorogood, M; Griffiths, F; Munday, S; Stables, D (2008)
Targeted cardiovascular disease prevention relies on risk-factor information held in primary care records. A risk algorithm, the 'e-Nudge', was applied to data from a population of >or=50-year-olds in 19 West Midlands practices, to identify those individuals at risk of cardiovascular disease. Altogether, 5.9% were identified aged 50-74 years at >or=20% 10-year risk based on existing data, and a further 26.4% were potentially at risk but had missing risk-factor information; 9.2% of patients aged over 50 years with established cardiovascular disease had at least one modifiable risk factor outside the audit target of the Quality and Outcomes Framework. Implications for resource allocation are discussed.